Effect of chewing gum on the postoperative recovery of gastrointestinal function after gynaecological laparoscopic surgery - Bhatiyani, Binti; ., Pandeeswari; Bhasani, Dolly; Dhumale, Shrikant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The incidence of postoperative ileus (POI) after gynaecological surgery is 10-15%. Chewing gum following general surgery improves outcomes, including early flatus, early bowel sounds, and shortening of the hospitalisation period. This study aims to investigate the effect of postoperative gum chewing on bowel motility after laparoscopic gynaecologic surgery. Methods: 101 women who underwent laparoscopic surgery for benign gynaecological conditions under general anaesthesia were recruited. 50 patients received sugar free chewing gum post operatively and the outcomes were compared with the control group. The study’s primary end points were the time to first regular bowel sounds and time to passage of flatus after surgery. Secondary end points were the time to first defecation, patient satisfaction, and potential side effects of postoperative gum chewing. Results: We found a significantly shorter interval between surgery and passage of flatus in the intervention group (median 10 hours compared with 13 hours p=0.0151) and a significantly higher rate of regular bowel sounds 3 hours (74% compared with 45%; p= 0.003) and 5 hours after surgery (91% compared with 78%; p=0.01). There was no significant difference in time to first defecation between groups (median 18 hours compared with 20 hours; p=0.222). Conclusions: Gum chewing seems to have beneficial effects on bowel motility when used in postoperative care after minimally invasive surgery. Gum chewing should be recommended to patients after gynaecological laparoscopic surgery